2013
DOI: 10.3402/gha.v6i0.20100
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of the health status of the United Arab Emirates: the ‘Big 4’ public health issues

Abstract: BackgroundThe United Arab Emirates (UAE) is a rapidly developing country composed of a multinational population with varying educational backgrounds, religious beliefs, and cultural practices, which pose a challenge for population-based public health strategies. A number of public health issues significantly contribute to morbidity and mortality in the UAE. This article summarises the findings of a panel of medical and public health specialists from UAE University and various government health agencies commiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
95
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 108 publications
(111 citation statements)
references
References 7 publications
1
95
0
Order By: Relevance
“…10% of all deaths due to cardiovascular diseases, 22% of all cancer deaths and 36% of all deaths from diseases of the respiratory system are attributed to tobacco use (WHO, 2012). Cardiovascular diseases are increasing globally as well as UAE and it is a leading cause of death in the UAE (HAAD health statistics, 2011;Hajat et al, 2012) and of the "Big four" public health issues identified in the UAE (Loney et al, 2013) three of them viz. cardiovascular disease, cancers and respiratory disorders have direct links to smoking, thereby making it a number one priority issue to be addressed urgently.…”
Section: Introductionmentioning
confidence: 99%
“…10% of all deaths due to cardiovascular diseases, 22% of all cancer deaths and 36% of all deaths from diseases of the respiratory system are attributed to tobacco use (WHO, 2012). Cardiovascular diseases are increasing globally as well as UAE and it is a leading cause of death in the UAE (HAAD health statistics, 2011;Hajat et al, 2012) and of the "Big four" public health issues identified in the UAE (Loney et al, 2013) three of them viz. cardiovascular disease, cancers and respiratory disorders have direct links to smoking, thereby making it a number one priority issue to be addressed urgently.…”
Section: Introductionmentioning
confidence: 99%
“…Results of the combined data from the these trials revealed that evolocumab significantly reduced the concentration of LDL cholesterol by 61%, from a median of 120 mg per deciliter to 48 mg per deciliter compared with standard therapy alone (P<0.001). The rate of cardiovascular events at 1 year was reduced from 2.18% in the standard-therapy group to 0.95% in the evolocumab group (hazard ratio in the evolocumab group, 0. become a public health problem in emerging countries, hence these agents could be important for prevention of risk of CAD including acute coronary syndromes and in all countries [5][6][7][8][9][10][11][12] .…”
Section: Phase 3 Trials On Cardiovascular Outcomesmentioning
confidence: 99%
“…3 The UAE population has grown substantially over the past 4 decades (census population estimates: 557,887 in 1975, 4.1 million in 2005, 8.3 million in 2010), and this is primarily due to high net inward migration of expatriate workers and the high natural growth of the Emirati population. 1,3 Mass recruitment of migrant workers has created an unusual population structure as the native Emirati population constitutes approximately 11% (~950,000) of the total UAE population and the remainder is composed of multinational expatriates. 3 Moreover, the UAE population has a youthful age distribution; for example, in the emirate of Abu Dhabi (largest emirate in terms of population size; 2,334,563 in 2010) 49% of the native Emirati population, 15% of the expatriate population, and 22% of the total UAE population were under the age of 19 years in the year 2010.…”
mentioning
confidence: 99%
“…3 Moreover, the UAE population has a youthful age distribution; for example, in the emirate of Abu Dhabi (largest emirate in terms of population size; 2,334,563 in 2010) 49% of the native Emirati population, 15% of the expatriate population, and 22% of the total UAE population were under the age of 19 years in the year 2010. 1,3 Over the past 4 decades there has been a shift from a traditional seminomadic physically active lifestyle to a modern, urbanized, and technology-driven lifestyle characterized by reduced occupational, domestic, and leisure-time physical activity (PA), coupled with the overconsumption of energy-dense convenience foods with poor nutritional content. 1 Consequently, there has been a dramatic increase in the prevalence of obesity, diabetes, and cardiovascular disease in both the indigenous Emirati and expatriate adult population.…”
mentioning
confidence: 99%
See 1 more Smart Citation